Use of Electronic Resources and its Impact: A Study of Dhaka University Library Users - Habiba, Umme; Chowdhury, Salma (Eastern Librarian, 2012)
This paper presents and analyses the status of electronic resources facilities and services provided by the Dhaka University Library (DUL). It also discusses the purpose of using e-resources, benefits, subject coverage status, overall user satisfactions, problems that are faced by DUL users while accessing e-resources and perceived impact of e-resources on users. Finally, it reports the results from questionnaire-based survey of e-resources use and its impact on DUL users. DOI: http://dx.doi.org/10.3329/el.v23i1.12122 Eastern Librarian Vol.23(1) 2012 pp.74-90